Александр Николаевич Скрябин - Бэлза Игорь Федорович (Русские и советские композиторы, 1983)
Экземпляры: ХР (20180709) / Инвентарный номер: 7989 / Цена: 0.90 / Авт.знак: Б97 / ГРНТИ: 18 / ББК: 85.313(2)